SYSTEMATIC LITERATURE REVIEW: MENINGKATKAN KREATIVITAS SISWA SEKOLAH DASAR MELALUI MIND MAPPING DENGAN MENGGUNAKAN ARTIFICIAL INTELLIGENCE - Nararrya Putri, Umi Laili; Muhid, Abdul; Niken Titi Pratitis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the use of Artificial Intelligence (AI)-based mind mapping in enhancing the creative thinking skills of elementary school students through a Systematic Literature Review (SLR) approach. Mind mapping, as a creative and interactive learning tool, is combined with AI technology to provide a more engaging and effective learning experience. The literature review findings indicate that integrating AI into mind mapping can enhance students' creativity, comprehension of materials, and engagement in the learning process. Additionally, the study identifies challenges and solutions in implementing this method, including the need for teacher training and the development of relevant learning media. Therefore, AI-based mind mapping holds significant potential for supporting more adaptive and effective educational innovations.